Convergencias paralelas: desafíos, desamores, desatinos entre antropología y comunicación - Jorge A. González (Estudios sobre las Culturas Contemporáneas, 2000)
The author employs tliree themes of discussion to point to a series of challenges to understanding processes of communication between the social sciences and anthropology: a) history and tecluiology in the world-system, b) the problematic question of the so<alled "media" and c) a conceptual guide expanded to understand communication as a process of coordination of conduct that presupposes but is not exliausted in semiosis. The text concludes with tlie identification of a number of challenges in each area and with the proposal of a model for studying the processes of teclmologically mediated communication.